Training of Minds and Souls: An Exploratory Study to Initiate Personal Change and Effective Problem Solving - Rodrigue Fontaine (Journal of Islamic Management Studies, 2022)
This study explores the usefulness of replacing automatic negative thoughts (ANTs). ANTs are irrational thoughts that seem to simply appear in one’s mind. These thoughts often reflect a fear and they prevent action. They create a self-fulfilling prophecy. ANTs are often associated with cognitive behavioral therapy (CBT), a technique used by some clinical psychologists to help clients. The literature suggests that CBT – which emphasizes “cognitive restructuring”- is compatible with the Islamic perspective. The literature on ANTs in the management literature is quite limited. This study would fill that gap. A group of 117 undergraduate students spent one semester learning to replace ANTs, change their behaviour and solve other people’s problems. The discussion focuses on the relevance of these skills to Muslims.